Modelling and parametic study of externally presstressed beams at ultimate limit state - Wong, Woan Jiuan (Universiti Malaysia Sarawak, UNIMAS, 2006)
In recent years, the use of external prestressing technique has been growing rapidly in upgrading and strengthening existing structures, especially bridge girders. However, the structural behaviour of beams prestressed with external tendons is still not fully understood and insufficient studies were carried out as compared to internal bonded prestressing. The complexity in the analysis of externally prestressed beams are: (i) stress increase in the external tendons is depending on the overall deformation of the structural member; and (ii) eccentricity variations of external tendons under load, commonly referred to as second-order effects.